Klotho: An Elephant in Aging Research. (7th March 2019) - Cheikhi, Amin; Barchowsky, Aaron; Sahu, Amrita; Shinde, Sunita N; Pius, Abish; Clemens, Zachary J; Li, Hua; Kennedy, Charles A; Hoeck, Joerg D; Franti, Michael; Ambrosio, Fabrisia
Abstract: The year 2017 marked the 20th anniversary of the first publication describing Klotho. This single protein was and is remarkable in that its absence in mice conferred an accelerated aging, or progeroid, phenotype with a dramatically shortened life span. On the other hand, genetic overexpression extended both health span and life span by an impressive 30%. Not only has Klotho deficiency been linked to a number of debilitating age-related illnesses but many subsequent reports have lent credence to the idea that Klotho can compress the period of morbidity and extend the life span of both model organisms and humans. This suggests that Klotho functions as an integrator of organ systems, making it both a promising tool for advancing our understanding of the biology of aging and an intriguing target for interventional studies. In this review, we highlight advances in our understanding of Klotho as well as key challenges that have somewhat limited our view, and thus translational potential, of this potent protein.